English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Simplify this expression (3x + 1)^2 + (2x - 7)^2 please help with this thanks a bunch

2007-05-21 07:30:22 · 2 answers · asked by delphiniums 1 in Science & Mathematics Mathematics

2 answers

(3x + 1)² + (2x - 7)²

= 9x² + 6x + 1 + 4x² - 28x + 49

= 13x² - 22x + 50

2007-05-21 07:37:25 · answer #1 · answered by fred 5 · 0 0

= (3x + 1).(3x + 1) + (2x - 7).(2x - 7)
= 9x² + 6x + 1 + 4x² - 28x + 49
= 13 x² - 22 x + 50

2007-05-21 14:48:29 · answer #2 · answered by Como 7 · 0 0

fedest.com, questions and answers